The cosmopolitan constitution - Somek, Alexander (Oxford : Oxford University Press, 2014)
This book looks at the changes of the foundations of constitutional authority since the eighteenth century. Somek argues that post WWII, people are no longer the fountain of authority, instead the new commitment to human rights and the 'peer review system' among nations, marks the advent of the cosmopolitan constitution.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 23, 2014).
Keywords: Constitutions; Constitutional law; Constitutional history